A relationship that makes life worth-living: levels of value orientation explain differences in meaning and life satisfaction. Issue 1 (January 2022) - Besika, Anastasia; Schooler, Jonathan W.; Verplanken, Bas; Mrazek, Alissa J.; Ihm, Elliott D.
Abstract: When people talk about their values they refer to what is meaningful to them. Although meaning is associated with life satisfaction, previous studies report inconsistent results regarding the association of values and well-being. A cross-sectional study ( N = 276) addresses the research question, do values influence experiences of meaning and subjective evaluations of life satisfaction? To assess whether providing a definition of "meaningful" is necessary when employing meaning measures, we assigned participants to condition where some provided their definition and others read a definition of "meaningful". All participants described a recent meaningful experience; they characterized it with sources of meaning; they read descriptions of 10 values and assessed the degree those were relevant to their experience; and they completed meaning and life satisfaction measures. Findings, which were unaffected by reading a definition of "meaningful", indicated that the most common source of meaning (Family) was associated positively with the value of Tradition and negatively with the value of Universalism. Latent Profile Analysis identified three profiles denoting participants' level of value orientation, which explained interindividual differences in average levels of meaning and life satisfaction variables. Participants who associated their meaningful experience with the 10 universal values at a high level scored higher in the meaning and life satisfaction measures than those who associated their experience to the 10 universal values at a low level. The present work advances knowledge regarding the relationship between meaning, values and life satisfaction and validates previous studies reporting on meaning as a marker of well-being. Abstract : Latent value profiles, Meaning in life, Sources of meaning, Latent profile analysis, Satisfaction with life, Well-being.